The Impact of Accent Second Language on Listening Comprehension - Amru, Aisyah; Sakinah, Nasywa; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2024)
This study aims to investigate the impact of accent on a second language and the impact of accent on second language listening comprehension. Utilizing an experimental approach, we collected data from the group of participants exposed to different accents in the context of teaching English as a second language. Data analysis methods involved evaluating listening comprehension through tests and interviews. The results indicate that specific accents can influence the level of listening comprehension, with significant implications for second language teaching and curriculum material development.